2009
DOI: 10.1016/j.seizure.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of refractory epilepsy in childhood

Abstract: Risk of developing refractory epilepsy is very low in idiopathic syndromes. For the rest of patients, a simple model comprising three variables allows more accurate prediction of risk of refractoriness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Its occurrence in early childhood was strongly correlated with later drug resistance (Cramer's V = 0.6). Studies by other authors such as Sillanpaa [6], Ramos-Lizana et al [8], Mohanraj and Brodie [10], and Gurruraj et al [13] also revealed the relation between status epilepticus and drug-resistant epilepsy.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Its occurrence in early childhood was strongly correlated with later drug resistance (Cramer's V = 0.6). Studies by other authors such as Sillanpaa [6], Ramos-Lizana et al [8], Mohanraj and Brodie [10], and Gurruraj et al [13] also revealed the relation between status epilepticus and drug-resistant epilepsy.…”
Section: Discussionmentioning
confidence: 83%
“…In our study this was also one of the most influential risk factors for drug-resistant epilepsy (Cramer's V = 0.62). This view is shared by most authors [6,8,13,22,25]. According to Camifield, normal intellectual development is fundamental for good prognosis in epilepsy [26].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Sillanpaa found patients having refractory epilepsy had high initial seizure frequency 22 . In a recent study, a model comprising these variables (etiology, age at onset of epilepsy and number of seizures during first 6 months after diagnosis) had classified patients in groups with low, intermediate and high risk of refractory epilepsy 23 . This study showed that patients with a previous history of status epilepticus, prenatal insult, delayed mile stones and significant head trauma are at risk of uncontrolled seizure.…”
Section: Discussionmentioning
confidence: 99%